A unique antiphospholipid assay recognizing phospholipid mixture compared with criteria antiphospholipid immunoassays in lupus patients. (May 2017) - Zuo, Y; Willis, R; Papalardo, E; Petri, M; Harris, E N; Schleh, A; DeCeulaer, K; Smikle, M; Vilá, L M; Reveille, J D; Alarcón, G S; Gonzalez, E B
Background: While essential for the classification of antiphospholipid syndrome (APS), anticardiolipin (aCL) assays lack specificity and anti-β2glycoproteinI (anti-β2GPI) assays lack sensitivity in this regard. Our aim was to perform a comparative analysis of the APhL ELISA assay (IgG/IgM) and criteria antiphospholipid (aPL) immunoassays in identifying APS-related clinical manifestations in a large group of patients with systemic lupus erythematosus (SLE). Methods: Serum samples from 1178 patients from the Hopkins ( n = 543), LUMINA ( n = 588) and Jamaican SLE cohorts ( n = 47) were examined for IgG/IgM positivity in aCL (in-house), anti-β2GPI (two commercial kits) and APhL (Louisville APL) ELISA assays. Correlation of assay positivity with clinical manifestations and sensitivity, specificity, positive and negative predictive values and likelihood ratios were evaluated. A case series analysis was also performed in patients for whom there was isolated positivity in the specific aPL assays. Results: The prevalence of aCL positivity was 34.9%, anti-β2GPI kit A was 22.6%, APhL was 11.5% and anti-β2GPI kit B was 7.6% in the study population. Anti-β2GPI kit B, aCL and APhL assays were correlated with venous thrombosis, while only APhL was significantly correlated with arterial thrombosis and consistently correlated with pregnancy-related morbidity. No significant correlations were noted for anti-β2GPI kit A. Sensitivity was greatest for aCL assays followed by anti-β2GPI kit A, APhL and anti-β2GPI kit B, while specificity was greatest and equal for anti-β2GPI kit B and APhL assays. Conclusions: Overall, APhL antibodies, especially IgG, represent a promising biomarker for the classification of APS patients in the context of autoimmunity and in risk assessment with regards to pregnancy morbidity and thrombotic manifestations.